2022
DOI: 10.3390/gels8080525
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Iron Minerals on the Compressive Strengths and Microstructural Properties of Metakaolin-Based Geopolymer Materials

Abstract: The current study aims to investigate the influence of iron minerals on the amorphous phase content, compressive strengths and the microstructural properties of the geopolymer materials. Geopolymer materials were prepared by the substitution of metakaolin by 10 and 20 wt.% of each iron mineral sample. Sodium waterglass from rice husk ash was used as a hardener, and metakaolin was used as an aluminosilicate source. The X-ray patterns show that the iron minerals denoted FR and FB are associated with hematite and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
2
0
2
Order By: Relevance
“…The iron source in the form of hematite, designation F, was supplied by Serraciments Company (Barcelona, Spain). This iron oxide has been used by Ngnintedem et al [8] as an additive for the synthesis of geopolymer materials. They reported that the broadening of the peak shows that the average size of the crystals of hematite is 120 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The iron source in the form of hematite, designation F, was supplied by Serraciments Company (Barcelona, Spain). This iron oxide has been used by Ngnintedem et al [8] as an additive for the synthesis of geopolymer materials. They reported that the broadening of the peak shows that the average size of the crystals of hematite is 120 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Eggshell, bauxite, and rice husk ash are used as sources of calcium, alumina, and silica, respectively, for the preparation of additives. The effect of different iron minerals such as hematite, magnetite, and goethite on the compressive strength of geopolymer cement was investigated by Ngnintedem et al [8]. It was reported that a 10 wt% addition of hematite to metakaolin resulted in a compressive strength of 56 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Iron oxide, like hematite powder, has been reported to act as a filler by several authors. 17 Several authors have reported that iron oxide, as well as hematite powder, contained in or added to feedstocks used to synthesise geopolymer materials, acts as a filler. The result is that there is no dissolution of the hematite during the geopolymerisation process.…”
Section: Introductionmentioning
confidence: 99%
“…A composição mineralógica do material de partida influencia em uma maior resistência do geopolímero, que pode ser obtida quando apresentam uma alta taxa de dissolução ou através da calcinação das matériasprimas [13]. Outro exemplo, o teor de ferro presentes em minerais de ferro como hematita, magnetita, maghemita, goethita, limonita e entre outros, que são encontrados em quantidades significativas de fontes de aluminossilicatos, também afetam as propriedades mecânicas dos geopolímeros [14].…”
Section: Introductionunclassified
“…O comportamento do ferro na reação de geopolimerização depende de qual estado físico e mineralógico o ferro está contido na matéria-prima [21,22]. NGNINTEDEM et al [14] investigaram a influência de três minerais de ferro, sendo estes a hematita, magnetita e goetita, na resistência à compressão em materiais geopoliméricos à base de metacaulim. Foi observado uma maior resistência nos geopolímeros contento hematita e magnetita em comparação com os contendo goetita.…”
Section: Introductionunclassified